Uniformity of air flow from the ceiling diffuser by an advanced design of the equalizing element in the plenum box with side entry. (27th May 2020) - Vasic, Mihailo; Stevanovic, Vladimir D.; Zivkovic, Branislav
Abstract : The main purpose of ventilation system is to meet the requirements of thermal comfort and air quality for the occupants. HVAC designers select air supply devices by using manufacturers' data, under the assumption that the outflow from the elements is uniform and radially symmetric. Uniformity and symmetry hold only if air velocity vectors have uniform intensities and directions that are perpendicular to the diffuser inlet cross section. Unfortunately, these conditions are hardly met in the engineering practice. The most common case of diffuser installation is the flush ceiling installation, accompanied with the plenum box with side entry above the ceiling. Therefore, in the present article investigated is the influence of different geometries of the equalizing elements in the plenum box with the side entry connection on the symmetry of the jet and the flow distribution through the four-sided square ceiling diffuser. New designs of the plenum box with an inclined non-uniformly perforated plate and with an equalizing element with air guidance blades are proposed and evaluated numerically and experimentally. A better uniformity of the air discharge from the diffuser outlet to the ventilated room is achieved.